Surface modifications induced by ns and sub-ps excimer laser pulses on titanium implant material - Bereznai Miklós; Pelsőczi-Kovács István; Tóth Zsolt; Laczkóné Turzó Kinga Mónika; Radnai Márta; Bor Zsolt; Fazekas András (2003)
Medical implants used in oral and orthopaedic surgery are mainly produced from titanium. Their biological behaviour, e.g. osseointegration, essentially depends on both the chemical composition and the morphology of the surface. Modifications achieved by excimer laser irradiation of titanium samples were investigated in order to improve their surface characteristics so as to facilitate biointegration. To enlarge the effective interfacial area of bone-implant contact, holes were ablated by laser pulses of ns or sub-ps length. During ns ablation, crown-like projecting rims formed around the borders of the holes. Ultra-short (0.5 ps) KrF excimer laser pulses were successfully applied to avoid these undesirable formations. Since a smooth dental implant surface is necessary to maintain a healthy connection with the soft tissues, laser polishing of samples was investigated, too. Irradiation with a series of ns laser pulses resulted in effective smoothing, as measured with atomic force microscope. X-ray photoelectron spectroscopy analysis of the laser-polished titanium surface revealed that laser treatment led to a decrease of the surface contamination and in thickening of the oxide layer. X-ray diffraction measurements demonstrated that the original alpha-titanium crystal structure was preserved. (C) 2003 Elsevier Science Ltd. All rights reserved.